Impact of a fall in the elderly: an analysis of the risk factors - Lima, Deivson Wendell da Costa; Cruz, Alyne Mara Maia; Morais, Fabíola Maria Pitombeira de; Torres, Arthur Dyego de Morais; Freitas, Maria Célia de (Rev Rene, 2013)
One aimed to identify the risk factors associated to falls in the elderly, which reflect on their quality of life. This is a descriptive, cross-sectional study. A questionnaire was used to collect data from older adults of an active living group from Russas-CE during the period from August to December 2011. The data were inserted in electronic spreadsheets, analyzed by the descriptive statistics and submitted to odds ratio and chi-square tests with significance level p<0.05. The results indicate a high prevalence of falls in the elderly, especially women (OR:14.636; CI- 2.82-75.954). The intrinsic significant factors were hearing problems (p=0,02) and foot problems (p=0,01). The extrinsic factors were steps in the door (17%), resulting in fractures of the upper limb (69%), morbidity (41%) and psychological complaints (70%). Therefore, it is necessary the development of preventive and rehabilitation actions, ensuring a better quality of life for the elderly. DOI:https://doi.org/10.15253/2175-6783.2013000500009